Pembelajaran Kooperatif Tipe Active Debate Terhadap Kemampuan Berargumentasi Siswa - Mulyani, Rizqi; Irwan, Irwan; Pandapotan Simaremare, Tohap (Citizenship Education, Faculty of Education, Jambi University, 2024)
This study aims to analyze how to improve the argumentation ability of Civics class students at SMP Negeri 5 Kuala Tungkal by using the active debate type cooperative learning model. This study uses a true experimental design and quantitative experimental methodology. The research instrument is Posttest-Only Controlled Design. This investigation was conducted at SMP Negeri 5 Kuala Tungkal. Eighth grade students, in three classes and sixty people, became the sample for this study. Class VIIIA as the experimental group, then class VIIIB as the control group; Posttest data analysis showed that Ha was accepted and Ho was rejected. This is evidenced by tcount> ttable = 7.613> 1.683, and a sign value (2-tailed) of 0.00 <0.05 for students' argumentation ability. So the active debate model has an effect on the argumentation ability of class VIII students of SMP Negeri 5 Kuala Tungkal to argue about matters related to Civics.